Everything you always wanted to know about puberty -- and shouldn't be Googling : for curious boys - Katz, Morris, 1999- (Downtown Bookworks, 2020)
This is the puberty book written by the cool, older brother--that takes boys from their first armpit hair to their first wet dream--and beyond. Facts about developmental changes to tween and teen boys' bodies and brains are spelled out in fun, familiar, boy-speak and illustrated in edgy graphic novel format. So boys 10 and up can learn about health, hygiene, sexuality, and more in a way that's not embarrassing or tedious, but real, engaging, and enlightening. A recurring "Puberty Goggles" feature pokes gentle fun at the way a testosterone-tormented tween views himself and the world around him. The book also explores current hot-button topics from social media and cyberbullying to respecting women. --